Good Corporation, Bad Corporation Corporate Social Responsibility in the Global Economy - Jimenez, Guillermo C.; Pulos, Elizabeth (Open textbook library., 2016)
This textbook provides an innovative, internationally oriented approach to the teaching of corporate social responsibility (CSR) and business ethics. Drawing on case studies involving companies and countries around the world, the textbook explores the social, ethical, and business dynamics underlying CSR in such areas as global warming, genetically modified organisms (GMO) in food production, free trade and fair trade, anti-sweatshop and living-wage movements, organic foods and textiles, ethical marketing practices and codes, corporate speech and lobbying, and social enterprise. The book is designed to encourage students and instructors to challenge their own assumptions and prejudices by stimulating a class debate based on each case study.